Vasculotropic effects of calcimimetics - Koleganova, Nadezda; Piecha, Grzegorz; Ritz, Eberhard (Current opinion in nephrology and hypertension, 2010)
At all stages of chronic kidney disease (CKD) cardiovascular death is the most prominent cause of mortality. Current treatment options are still not completely satisfactory in this group of high cardiovascular risk patients. Experimental data and clinical observations suggest a role of secondary hyperparathyroidism, hyperphosphatemia, and hypercalcemia in the genesis of cardiovascular complications of CKD. The ubiquitous expression of the calcium-sensing receptor, which is targeted by calcimimetics and the pleiotropic effects of calcimimetics, make this class of drugs potential candidates for cardiovascular intervention.
Gesehen am 21.03.2023